Synthesis of thieno-bridged porphyrins: Changing the antiaromatic contribution by the direction of the thiophene ring - Mitsushige, Yusuke; Yamaguchi, Shigeru; Lee, Byung Sun; Sung, Young Mo; Kuhri, Susanne; Schierl, Christoph; Guldi, Dirk Michael; Kim, Dongho; Matsuo, Yutaka (Journal of the American Chemical Society, 2012)
Two types of thieno-bridged porphyrins were synthesized by incorporating a thiophene group across their meso and β positions with different directions of the thiophene ring to investigate the aromaticity of these porphyrins with extended π-systems. The 2,3-thieno-bridged porphyrin showed a larger antiaromatic contribution than did the 3,4-thieno-bridged porphyrin. In the former, the antiaromatic contribution is based on a 20-π-electron conjugated circuit. The two thieno-bridged porphyrins were characterized by calculations of nucleus-independent chemical shift and anisotropy of the induced current density as well as by X-ray crystallography, NMR spectroscopy, UV-vis-NIR absorption spectroscopy, electrochemical studies, time-resolved excited-state analysis, and two-photon absorption cross section measurements. Chemical derivatization of the 2,3-thieno-bridged porphyrin was also demonstrated. © 2012 American Chemical Society.